(untitled) (UNED Research Journal, 2025)
Introduction: Motivation is an essential factor in language learning, although its study still presents gaps, especially in Latin America. This phenomenon is complex and responds to personal and contextual factors that influence learner behavior. Motivation may originate from personal satisfaction or external pressures, highlighting the importance of environments that promote autonomy and perseverance. Motivated students tend to trust their abilities, participate actively, and experience less anxiety when facing new challenges. Objective: Our objective was to determine the relationship between motivation and English language learning in undergraduate students of early childhood education. Methods: The study was conducted at a higher education institution in Lima, Peru, with 60 early childhood education students, mostly women, during the 2025-I semester. The Likert scale for motivation and English learning was based on expert judgment, and its reliability reached high Cronbach’s alpha values. Participation was voluntary. Results: Ninety-three percent of the students reported high motivation, 5% moderate motivation, and 2% low motivation. Ninety-two percent achieved high levels of learning, 7% moderate, and 2% low. A strong positive correlation was found between motivation and English learning, supporting the study’s main hypothesis. Correlations of varying magnitudes were also observed with goal achievement and text production, while no significant association was found with comprehension of language skills. Conclusions: We conclude that motivation is an important factor in English learning, but its effects are not uniform across all dimensions of learning. These results highlight the need to design differentiated pedagogical strategies that foster motivation and specifically strengthen the comprehension of language skills. Keywords: academic performance, higher education, student perceptions, language instruction, education faculty, statistical tools